y-11=(5/11)(x-10)

Simple and best practice solution for y-11=(5/11)(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-11=(5/11)(x-10) equation:


x in (-oo:+oo)

y-11 = (5/11)*(x-10) // - (5/11)*(x-10)

y-((5/11)*(x-10))-11 = 0

(-5/11)*(x-10)+y-11 = 0

y-5/11*(x-10)-11 = 0

y-5/11*(x-10)-11 = 0

y-5/11*x-11+50/11 = 0

y-5/11*x-71/11 = 0

y-5/11*x-71/11 = 0

y-5/11*x-71/11 = 0 // - y-71/11

-5/11*x = -(y-71/11) // : -5/11

x = (-(y-71/11))/(-5/11)

x = -11/5*(71/11-y)

x = -11/5*(71/11-y)

See similar equations:

| 0.25(16-4x)=7-(1.25x+5) | | x-5y=17fory | | 4g+17=81 | | Xsquared+8x+15=0 | | 73774t+132=11 | | 4(2-3x)-(6x-4)=2(5-5x) | | h=32+48t-16t^2 | | 8n+19=4n+135 | | 2(3.14r)=20 | | 2x+8=25-9x | | 3*(X+2)=15 | | -6.1y=198.25 | | 12c-5c= | | w-16=28 | | 2/3x13 | | 5x^2+21x-4=0 | | -[-[-(6x+5)]]=-(x+5) | | 2(3p-t)-(-4p+t)= | | 24+p=54 | | 0.7r=-91 | | 6-6x=3y | | 11c+1=67 | | A(9+a)=4(2a+5) | | 54v^2+18v-120=0 | | r=f(w+a) | | Y(2)-3y+2=0 | | 13/10 | | 4.37=19p | | -2x=1/9 | | 8x-5y=66 | | 9(x+2)=9x+18 | | 16=n/3 |

Equations solver categories